THROMBOPHILIA KARENA DEFISIENSI PROTEIN C DAN PROTEIN S - Rama Putra, I Made; Suega, Ketut (journal of internal medicine, 2012)
Protein C is a natural anticoagulant, inhibits thrombin generation. Protein C de! ciency, is associated with a variably increased risk of thrombosis. Incidence of symptomatic protein C de! ciency is approximately 1 in 16,000 to 1 in 32,000 persons, similar in men and women. Morbidity in protein C de! ciency greatly increases with advancing age, when patients are at greater risk for thrombotic events such DVT, PE, postphlebitic and blindness secondary to vitreous hemorrhages may occur in patients with these severe conditions. The etiology can be inherited and acquired in a number of clinical scenarios include meningococcal septic shock; DIC; liver disease; or chemotherapy. Diagnostic base on personal history of venous thrombosis, thromboembolic events, abnormal laboratory coagulation tests. The laboratory workup should include haemostatic parameters, coagulation system such aPTT, PT, ! brinogen level and D-dimer test. A decreased protein C activity level is required. Imaging studies are appropriate for assessing the presence of thrombotic disease in a particular vessel. The treatment depends largely on a particular patient?s disease manifestations. Surgical treatment may be appropriate in some circumstances. We reported, a male Balinese 62 years old came with complain red vision and dull feeling since a moth prior to admission. No historical medical problem found. Physical exam found hypertension and laboratory ! nding showed slight dyslipidemia. Ophthalmologic examination revealed BRVO (Branch Retinal Vein Occlusion) ocular sinistra. Hypercoagulablae state are suspected. Hematologic exam revealed light hyperagregation and low level of protein C and protein S. Treated with heparin 5000 unit intravenously followed by drip 1000 unit per hour for 3 day continued with warfarin 4 mg OD reach INR 1.5 ? 2.5. Good resulted base on patient?s good compliance.
Keywords: protein C, protein S, BRVO, anticoagulant